2018
DOI: 10.1111/jnc.14610
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone up‐regulates glial fibrillary acidic protein via HB‐EGF secreted from astrocytes and neurons through PPARγ pathway and reduces apoptosis in high‐fat diet‐fed mice

Abstract: The anti-diabetic drug and peroxisome proliferator-activated receptor-gamma (PPARc) agonist, rosiglitazone, alters astrocyte activation; however, its mechanism remains less-known. We hypothesized participation of epidermal growth factor receptor (EGFR), known to control astrocyte reactivity. We first detected that rosiglitazone promoted glial fibrillary acidic protein (GFAP) expression in primary astrocytes as well as the mouse cerebral cortex, associated with increased EGFR activation. Screening for EGFR liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 73 publications
(90 reference statements)
3
10
0
Order By: Relevance
“…In both brain regions, GWE led to robust upregulation of GFAP (Fig 5A-5C). Notably, administration of ROSI resulted in enhanced GFAP expression ( Fig 5A-5C), as previously reported [79].…”
Section: Plos Onesupporting
confidence: 89%
“…In both brain regions, GWE led to robust upregulation of GFAP (Fig 5A-5C). Notably, administration of ROSI resulted in enhanced GFAP expression ( Fig 5A-5C), as previously reported [79].…”
Section: Plos Onesupporting
confidence: 89%
“…PPARs, a group of ligand‐activated TFs, have dual effect on the expression of GFAP gene, that is, facilitatory and inhibitory. For instance, activation of PPARγ with rosiglitazone increases GFAP expression in primary astrocytes of mouse cerebral cortex through transactivation of epidermal growth factor receptor (Kushwaha et al, ). Similarly, docosahexaenoic acid (DHA)‐enriched fish oil‐caused GFAP augmentation in rats also depends on the activation of PPARγ by increasing fatty acid‐binding protein‐7 (FABP7) expression (Tripathi et al, ).…”
Section: Expression Of Gfap and Its Regulationmentioning
confidence: 99%
“…Kushwaha et al[ 27 ] have indicated the existence of a rosiglitazone-induced anti-apoptotic effect on cerebral cortical tissue of high-fat-diet diabetic mice, for which the underlying mechanisms have not been clearly established. PPAR-γ mediated epidermal growth factor signaling appears to be the most probable pathway by which both glial and neural cells are affected.…”
Section: Antidiabetic Treatment and Neural Functionmentioning
confidence: 99%